2012
DOI: 10.1002/pip.1256
|View full text |Cite
|
Sign up to set email alerts
|

The complex material properties of chalcopyrite and kesterite thin‐film solar cell absorbers tackled by synchrotron‐based analytics

Abstract: In view of the complexity of compound semiconductor based thin‐film solar cells, which are comprised of a multitude of layers, interfaces, surfaces, elements, impurities, etc., it is crucial to characterize and understand the structural, chemical, and electronic properties of these components. Hence, this paper gives a review of our recent progress in the characterization of compound semiconductor thin films using synchrotron‐based characterization methods. It is demonstrated how different analytical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Sulfur was omitted because it was always in excess in the syntheses. There have been a few studies on the relationships between metal ratios and stoichiometries that produce secondary phases. ,,, Comparative ratios for copper, tin, and zinc that are indicative of higher quality CZTS that are utilized in solar cells achieving high efficiencies differ greatly . Typically Cu/(Zn + Sn) is expected to be between 0.9 and 0.96 and the Zn/Sn around 1.1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur was omitted because it was always in excess in the syntheses. There have been a few studies on the relationships between metal ratios and stoichiometries that produce secondary phases. ,,, Comparative ratios for copper, tin, and zinc that are indicative of higher quality CZTS that are utilized in solar cells achieving high efficiencies differ greatly . Typically Cu/(Zn + Sn) is expected to be between 0.9 and 0.96 and the Zn/Sn around 1.1 .…”
Section: Resultsmentioning
confidence: 99%
“…Neutron diffraction can be used , but requires comparatively large amounts of sample. The possibility to use anomalous diffraction at a synchrotron source to overcome this problem has largely been ignored until recently. Currently published articles either restrict themselves to qualitative changes or used single crystal data with limited explanatory power for realistic samples.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles studies showed that this quaternary phase is stable only within a very small domain of chemical potentials. , Slight deviations from optimal growth conditions result in spontaneous formation of undesired phases such as ZnS, SnS, SnS 2 , CuS, and Cu 2 SnS 3 rather than the desired CZTS phase. Critically, the first method of choice for distinguishing between possible nanocrystalline phases, powder X-ray diffraction (XRD), is of limited use here because CZTS and common impurities such as ZnS adopt very similar hexagonal wurtzite crystal structures (Figure ) (note: CZTS’s other well-known structure, tetragonal kesterite, was not observed here; neutron diffraction can provide better phase resolution but is less available). , Nevertheless, energy-dispersive X-ray spectroscopy (EDX) line scans on several nanorods prepared by the aforementioned procedure consistently showed marked axial composition gradients. Specifically, the amount of Cu increased, and the amount of Zn decreased from one side of the nanorods to the other (Figure ).…”
mentioning
confidence: 99%